New green HPLC and TLC methods for the determination of dapagliflozin, metformin hydrochloride, and its two official impurities, melamine and cyanoguanidine, in their quaternary mixture - Ibrahim, Nashwa Ahmed; Abd El Aleem, Eglal Abdelhamid; Abuelazem, Walaa Gamal; Abdelhamid, Nessreen Salah (European Journal of Chemistry, 2025)
Two environmentally friendly, simple, and accurate chromatographic methods were developed for the quantitative measurement of quaternary mixtures of dapagliflozin, metformin hydrochloride, melamine, and cyanoguanidine in both pure forms and pharmaceutical formulations. Recently, the development of new analytical methods requires taking into account green aspects. The principal objectives of green chemistry are the reduction and elimination of hazardous substances and their harmful effects on the environment and human health. The green HPLC method uses the C18 column (250 × 4.6 mm × 5 μm particle size) and a mobile phase consisting of methanol: water in a ratio of (90:10, by volume) with pH adjusted to 3.5 using o-phosphoric acid. The flow rate was 1.2 mL/min detected at 225 nm. Retention time (Rt) values were found to be 5.75, 2.06, 2.49 and 3.01 min for dapagliflozin, metformin hydrochloride, melamine, and cyanoguanidine, respectively, while the proposed green TLC method uses a silica gel plate 60F254 and ethanol: ethyl acetate (1:9, by volume) as a developing system detected at 225 nm. The Rf values were found to be 0.66, 0.74, 0.51 and 0.83 for the four components, respectively. Good linearity was shown through concentration ranges of 1-30, 2-70, 0.5-25, and 1-25 μg/mL for the four components, respectively, for the proposed HPLC method and 0.1-1.5, 0.2-3.0, 0.1-1.5 and 0.1-1.2 μg/band for the four components, respectively, for the proposed TLC method. The proposed methods were successfully applied to diaflozimet 10/1000® tablets containing dapagliflozin and metformin hydrochloride and the results were statistically compared to a published HPLC method and no significant differences were found.